Impact of cross-linking mode on the physical properties of zein/PVA composite films. (December 2018) - Liang, Jun; Chen, Ruipeng
Graphical abstract: Highlights: Hydrophobic zein and hydrophilic PVA were made into homogenous films by cross-linking. Mode of cross-linking lead to distinctly different physical property of composite films. Abstract: To study the impact of cross-linking mode on the physical properties of blended biomaterial matrices, zein/PVA was cross-linked with borate, tripolyphosphate or mixture of borate and tripolyphosphate, and the composite films were obtained by a casting of dispersion. Mechanical measurements indicated that different modes of cross-linking lead to varying degrees of film strength and the increase of elongation, while the films treated with borate and tripolyphosphate mixture show the best performance. Meanwhile, changes in the fractured sectional images showed a densified texture induced by cross linkers, especially for borate and tripolyphosphate mixture. FTIR showed the enhanced interaction between the matrix polymers treated by tripolyphosphate, confirmed by a slight increase in glass transitional temperature and a higher surface hydrophobicity compared with matrices treated by borate. Meanwhile, it has been found that the composite film treated with double cross-linking mode possessed the best thermal stability (i.e., highest T g value) and the highest surface hydrophobicity. The results showed that cross-linking modes had a significance on the physical properties of composite films and the ideal film improvements could be obtained by double cross-linking modes.